Mighty motivators a resource bank for setting targets and rewarding pupil progress for 5 to 11 year olds - Moore, Claire 1968-
Target setting has long been recognised as a positive way to involve young people in both planning for the future and evaluating their own progress. These resources encourage adults and children to work in partnership in setting a range of appropriate targets which will promote positive attitudes to learning and behaviour
"A Lucky Duck book"
Keywords: Motivation in education; Motivation in education -- Problems, exercises, etc; Achievement motivation in children; Achievement motivation in children -- Problems, exercises, etc